Teacher recruitment, selection, and promotion: the role of teachers’ unions in Malaysia - Syed Muhamad Ubaidillah, Syed Husin (Universiti Malaysia Pahang, 2020)
The topic reviews the roles of Teachers’ Unions in teacher recruitment, selection, and promotion and their impacts on the timely graduate teachers as well as to the educational system in general. The objectives of the research were to analyze the current situation in the Malaysia’s Ministry of Education from the Human Resource Management (HRM) point of view. It outlines the issues that exist within HRM particularly on the influence of teachers’ Unions in the formation of Human Resource policy in education on teachers’ recruitment channel , selection methods and promotion and its effects on the timely graduate teachers. Special reference was given to the latest Malaysia’s educational policy - Malaysian National Education Blueprint (2013-2025) which inter alia has included human resource management in its transformation program. We argue that Teachers’ Unions have their influence in the formation of policy by the Ministry of Education on recruitment, selection and promotion of teachers. How the policy benefits the college-qualified teachers and affect the timely graduate teachers in particular and the educational system in general.